Impact of Chronic Kidney Disease on Clinical Outcomes during Hospitalization and Five-Year Follow-Up after Coronary Artery Bypass Grafting - Mohamed Laimoud; Mosleh Nazzel Alanazi; Mary Jane Maghirang; Shatha Mohamed Al-Mutlaq; Suha Althibait; Rasha Ghamry; Rehan Qureshi; Boshra Alanazi; Munirah Alomran; Zeina Bakheet; Zohair Al-Halees (Critical Care Research and Practice)
Background. Chronic kidney disease (CKD) is often associated with multiple comorbidities including diabetes mellitus, and each has its own complications and impact after cardiac surgery including coronary revascularization. The objective of this work was to study the impact of CKD on clinical outcomes after coronary artery bypass grafting (CABG) and to compare outcomes in patients with different grades of renal functions. We retrospectively reviewed all patients who underwent CABG from January 2016 to August 2020 at our tertiary care hospital using electronic medical records. Results. The study included 410 patients with a median age of 60 years, and 28.6% of them had CKD and hospital mortality of 2.7%. About 71.4% of the patients had GFR > 60 mL/min per 1.73 m2, 18.1% had early CKD (GFR 30–60), 2.7% had late CKD (GFR < 30), and 7.8% of them had end-stage renal disease (ESRD) requiring dialysis. The CKD group had significantly more frequent hospital mortality (p = 0.04), acute cerebrovascular stroke (p = 0.03), acute kidney injury (AKI) (p < 0.001), longer ICU stay (p = 0.002), post-ICU stay (p = 0.001), and sternotomy wound debridement (p = 0.03) compared to the non-CKD group. The frequencies of new need for dialysis were 2.4% vs. 14.9% vs. 45.5% (p < 0.001) in the patients with GFR > 60 mL/min per 1.73 m2, early CKD, and late CKD, respectively. Acute cerebral stroke (OR: 10.29, 95% CI: 1.82–58.08, and p = 0.008), new need for dialysis (OR: 25.617, 95% CI: 13.78–85.47, and p < 0.001), and emergency surgery (OR: 3.1, 95% CI: 1.82–12.37, and p = 0.036) were the independent predictors of hospital mortality after CABG. The patients with CKD had an increased risk of strokes (HR: 2.14, 95% CI: 1.20–3.81, and p = 0.01) but insignificant mortality increase (HR: 1.44, 95% CI: 0.42–4.92, and p = 0.56) during follow-up. Conclusion. The patients with CKD, especially the late grade, had worse postoperative early and late outcomes compared to non-CKD patients after CABG. Patients with dialysis-independent CKD had increased risks of needing dialysis, hospital mortality, and permanent dialysis after CABG.